1995
DOI: 10.1148/radiology.197.3.7480771
|View full text |Cite
|
Sign up to set email alerts
|

Decreased acute toxicity by using midline mucosa-sparing blocks during radiation therapy for carcinoma of the oral cavity, oropharynx, and nasopharynx.

Abstract: Midline MSBs decrease acute toxicity during radiation therapy for carcinoma of the oral cavity, oropharynx, and nasopharynx without compromising tumor control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Previous studies have shown that a dose-effect curve has been obtained for the incidence and severity of mucositis. [1][2][3] It is important to remember that the rats were subjected to a single, relatively high dose of radiation whereas human patients receive radiotherapy as a series of fractionated or hyperfractionated doses. There were noticeable changes observed in the irradiated animals with respect to mucositis, body weight gain, and decrease in food intake, and these are shown in Figures 1, 2, and 3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that a dose-effect curve has been obtained for the incidence and severity of mucositis. [1][2][3] It is important to remember that the rats were subjected to a single, relatively high dose of radiation whereas human patients receive radiotherapy as a series of fractionated or hyperfractionated doses. There were noticeable changes observed in the irradiated animals with respect to mucositis, body weight gain, and decrease in food intake, and these are shown in Figures 1, 2, and 3.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of mucositis depends on many variables, such as anti-cancer treatment protocol, age, diagnosis of the patient, level of oral hygiene during therapy, and genetic factors. 1,2,3,4 Oral mucositis begins five to seven days after the initiation of radiotherapy with cumulative doses of about 10-15 Gy of standard fractionated radiation. Acute mucositis is defined as a reactive inflammation of the mucosa and atrophy of the squamous epithelial tissue and with an absence of vascular damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients should refrain from smoking. yes/yes/no P instructions on oral care significant reduction Rugg et al 32 no/no/no P smoking during RT higher mucositis incidence in smokers CT Greenberg et al 44 no/yes/no P dental treatment prior to CT significant reduction of septicemia CT+RT Sonis et al 36 no/no/no P early and aggressive reduced frequency of oral complications dental intervention BMT Peters et al 52 no/no/no P treatment of asymptomatic no difference in infectious complications periapical radiolucencies BMT Borowski et al 35 yes/yes/no P intensive vs. regular oral care significant reduction of mucositis but not septicemia b) Radiation shields RT Perch et al 106 no/no/no P midline mucosa sparing blocks decreased mucositis without affecting tumor control Keus et al 104 no/yes/no P customized beam shaping lower incidence of mucositis c) Soft lasers BMT Barasch et al 109 yes/yes/no P laser on one buccal side, significant reduction placebo light to the other Cowen et al 110 yes/yes/no P laser vs. no treatment significant reduction of incidence CT Ciais et al 107 no/yes/no P+T soft laser treatment lowers incidence and alleviates course of mucositis d) Cryotherapy CT Mahood et al 67 yes/yes/no P oral cryotherapy vs. no significant lower incidence prophylaxis Rocke et al 65 yes/yes/no P 30 vs. 60 minutes of equivalent cryotherapy during Cascinu et al 66 yes/yes/no P oral cryotherapy vs. no significant lower incidence prophylaxis Edelman et al 68 no/yes/no P ice chips during dose escalation lower incidence of mucositis of edatrexate Gandara et al 69 no/yes/no P ice chips during edatrexatelower incidence of severe mucositis based CT 2. Locally applied pharmacotherapeutics e) Mouth-coating agents Sucralfate CT Loprinzi et al 130 yes/yes/yes T sucralfate vs. placebo after no difference cryoprophylaxis RT Scherlacher et al 120 yes/yes/no P sucralfate vs. standard oral significant reduction of incidence and hygiene severity of mucositis Throughout treatment, elimination of apparent infectious foci, mostly through extraction of teeth with infected pulp, has to be emphasized-even in myelosuppressed patients.…”
Section: Oral Mucositis Complicating Chemotherapy And/or Radiotherapymentioning
confidence: 99%
“…One approach to reduce the severity of mucositis is to decrease the total dose of radiation and/ or the volume of mucosa treated. 83 Although this is possible in small tumors, it is not usually feasible in more advanced disease. On the other hand, it is now apparent that higher doses of radiation are required to control bigger tumors, which makes severe mucositis more likely.…”
Section: Discussionmentioning
confidence: 99%